2019
DOI: 10.1071/ah17090
|View full text |Cite
|
Sign up to set email alerts
|

HealthPathways improving access to care

Abstract: HealthPathways (HPW) is an international web-based information portal that provides health practitioners with guidelines and referral pathways to specialists and services. The present study explored usage of HPW by general practitioners (GPs) in the Barwon region, south-west Victoria, and any benefits and barriers to its use. Approximately 421 GPs provide services in 86 clinics across the Barwon region, south-west Victoria and Barwon Health is the public health service providing acute, subacute, residential ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…), online portal VOLUME 10 • NUMBER 3 • SEptEMBER 2018 J OUrNal OF PrimarY HealtH Care access, 25 systematic review of peer-reviewed and grey literature, 6 online survey questionnaire 26 or mixed-method approaches. 7,24 Qualitative research allowed a more nuanced understanding of the barriers and facilitators to acceptance and use of BNPs, facilitating deeper insight into GP uptake and engagement with BNPs, and showing how general practice is oriented towards improved patient experiences and outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…), online portal VOLUME 10 • NUMBER 3 • SEptEMBER 2018 J OUrNal OF PrimarY HealtH Care access, 25 systematic review of peer-reviewed and grey literature, 6 online survey questionnaire 26 or mixed-method approaches. 7,24 Qualitative research allowed a more nuanced understanding of the barriers and facilitators to acceptance and use of BNPs, facilitating deeper insight into GP uptake and engagement with BNPs, and showing how general practice is oriented towards improved patient experiences and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…24 Similar to other researchers, we found that opinion leaders and specialist involvement in the development and promotion of BNPs can be pivotal to uptake by GPs. 8,26 This not only improves primary-secondary care relationships, Gill et al 7 and Gray et al 25 also indicated that a comprehensive approach to Pathway implementation and service redesign can lead to improved access to specialist care. BNPs can be a centralised information hub, with local information at the users' fingertips.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While HealthPathways is not yet available in our local health district, use of the portal around Australia has been shown to improve the quality of referrals and access to care. 4 We found a significant amount of information lacking in GP referrals to our paediatric outpatient clinic. Using paediatricspecific referral guidelines could improve the quality of referrals, improve the triage process, reduce the number of rejected referrals and help patients receive timely, appropriate care.…”
mentioning
confidence: 90%